Dampak Pandemi Covid-19 Terhadap Dunia Pendidikan - Siahaan, Matdio (Jurnal Kajian Ilmiah, 2020)
Indonesia is one of the countries infected with the Covid-19 pandemic. Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled "Race Against the Virus, the Indonesian Consumer Response towards COVID-19" revealed that as much as 50% of Indonesian people began to reduce activities outside the home, and 30% of them said that they planned to shop more frequently online. Likewise, teaching and learning activities are carried out from home and even work is done from home with the aim of reducing Covid-19 epidemic. Key Words: Pandemic Covid-19, Distance Learning/Onlne, Education, Abstrak Indonesia merupakan salah satu negara yang terinfeksi pandemi Covid-19. Penyakit Corona virus 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh sindrom pernapasan akut corona virus 2 (SARS-CoV-2). Sehingga berdampak kepada Masyarakat dan Mahasiswa tidak bisa bertemu langsung di kampus atau di tempat umumu. Berdasarkan Riset Nielsen yang bertajuk â€œRace Against the Virus, Indonesian Consumer Response towards COVID-19â€ mengungkapkan bahwa sebanyak 50% masyarakat Indonesia mulai mengurangi aktivitas di luar rumah, dan 30% di antaranya mengatakan bahwa mereka berencana untuk lebih sering berbelanja online. Begitu juga kegiatan proses belajar mengajar dilaksanakan dari rumah bahkan bekerja pun dilakukan dari rumah dengan tujuan agar bisa mengurangi penularan Covid-19. Kaca Kunci: Penularan Covid-19, Belajar Jarak Jauh, Pendidikan.